Three-dimensional imaging of nanoplasma by momentum-to-position mapping - Xu Han; Jiawang Guo; Xiang Huang; Hao Huang; Xianglong Fu; Kunlong Liu; Qingbin Zhang; Peixiang Lu (APL Photonics, 2025)
Laser irradiated nanostructures generate nanoplasmas with ultrahigh energy densities, yet retrieving their three-dimensional (3D) spatial distribution remains challenging due to ion expansion and loss of original spatial information. In this study, we introduce a momentum-to-position mapping method to retrieve lost 3D information in position space of the ions from intense laser irradiated nanosphere, supported by ion momentum tomographic reconstruction and molecular dynamics (MD) modeling. Our results demonstrate pronounced variations in localized nanoplasma across the nanosphere surface for different irradiated intensities, providing experimental evidence for the combined action of external and internal fields on nanoplasma formation. This work represents an advanced correlation between ion emission in both momentum and position space, offering an intuitive 3D visualization of localized nanoplasma and facilitating potential applications based on nanoplasma manipulation.